2004
DOI: 10.1002/jhet.5570410101
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of carbazole, acridine, phenazine, 4H‐benzo[def]carbazole and their derivatives by thermal cyclization reaction of aromatic amines

Abstract: A variety of nitrogen-containing heterocycles were synthesized by passing vapors of aromatic amines over calcium oxide at 450-650 °C under nitrogen carrier gas. Reaction of 2-aminobiphenyl 3 a at 560 °C gave carbazole 4 in 80% yield. Reaction of 2,2'-diaminobiphenyl 3 b a fforded a mixture of carbazole 4 a n d 4-aminocarbozole 6 b. In the case of 2-amino-2'-nitrobiphenyl 3 c, benzo[c]cinnoline 7 was obtained along with carbazole 4. Reaction of 2-amino-2'-methoxybiphenyl 3 d gave four products of carbazole 4, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The same year, Gajula and co-workers [83] reported an efficient approach of using condensation method in one pot to synthesize of various substituted phenazine derivatives (43)(44)(45)(46)(47)(48)(49)(50). As shown in Scheme 8, in general, 2-naphtol occurred self-coupling to form the intermediate of 1, 2-naphthoquinones had condensation in one pot to obtain target compound in good to excellent yields.…”
Section: Benzo[a]phenazine and Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…The same year, Gajula and co-workers [83] reported an efficient approach of using condensation method in one pot to synthesize of various substituted phenazine derivatives (43)(44)(45)(46)(47)(48)(49)(50). As shown in Scheme 8, in general, 2-naphtol occurred self-coupling to form the intermediate of 1, 2-naphthoquinones had condensation in one pot to obtain target compound in good to excellent yields.…”
Section: Benzo[a]phenazine and Derivativesmentioning
confidence: 99%
“…In sharp contrast, these synthetic strategies epitomize powerful alternatives with sustainable, facile, and highefficient principles for the formation of complex molecules, such as electrochemical strategy, biosynthesis, microwave method, supramolecular catalysis, photocatalysis, and some chemical synthesis [16,[44][45][46][47][48][49][50][51][52][53][54][55][56]. Notably, these strategies effectively avoid the major drawbacks of traditional methods and simultaneously provide concise process to furnish structurally various phenazine derivatives in good to excellent yields [49,[57][58][59][60][61][62][63].…”
Section: Introductionmentioning
confidence: 99%
“…The dehydrogenation was used to synthesize 4H-benzo[def]carbazole [7]. In the previous paper [8], we reported that dehydrogenation of aromatic amines by calcium oxide is a powerful method to prepare five-and six-membered heterocycles such as carbazole, acridine, phenazine and 4H-benzo[def]carbazole from 2-aminobiphenyl, 2aminodiphenylmethane, 2-aminodi-phenylamine and 4aminophenanthrene.…”
Section: Introductionmentioning
confidence: 99%
“…1, Scheme 1). [5] From the point of green and sustainable chemistry, there are currently three generations regarding to the CÀ H bond amination strategy. Firstly, transition-metal-catalyzed (Rh, [6] Ir, [7] Pt, [8] Pd, [9] Cu [10] ) CÀ H bond activation of N-substituted 2-aminobiaryl enables carbazole synthesis with the assistance of chemical oxidants (Eq.…”
mentioning
confidence: 99%